Dengue Haemorrhagic Fever. A Problem of Clinical Diagnosis and Proposal for Using a Scoring Systetn - Munir, Muzief; Husada, Tjandra; Mustadjab, I. (Paediatrica Indonesiana, 1982)
This prospective study was conducted in an attempt to find out a method of clinical diagnoS’is of Dengue Haemorrhagic Fever wi,th high accuracy and coverage. A clinical picture of all cases admitted with 3 days fever of unknown origin and poS’itive tourniquet test was studied. The cardinal signs and symptoms i.e. liver enlargemerz.t, thrombocyte counJ. hematocrit, spontaneous bleeding such as epistaxis, petechiae, hematonw and hematemesis, were thoroughly studied from the day of admission up to the sixth day of illness. Blood was drawn into filter-paper disks for serologic examination on the day of admission, then 5, and 10 days thereafter. Based on a series of serological tests, the patients were grouped into confirmed and false DHF. Liver enlargement was found in both groups, but only in the confinned DHF group was it significantly related to the day of illness (r = 0.45, with probably error of 0.03 ).